1991
DOI: 10.1128/aac.35.2.390
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intrasubject variabilities in the pharmacokinetics of rufloxacin after single oral administration to healthy volunteers

Abstract: Rufloxacin is a new long-acting, once-daily quinolone antibacterial agent. We evaluated inter-and intrasubject variations in pharmacokinetics of rufloxacin following oral administration of 400 mg (two capsules) under controlled conditions, at an interval of 2 weeks (periods I and II), to 12 healthy male subjects. Plasma and urine samples were collected up to 48 h after drug administration. Plasma drug levels determined by bioassay were higher than those measured by high-performance liquid chromatography, indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
28
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 5 publications
6
28
0
Order By: Relevance
“…(15). It has excellent serum and urine concentrations and a particularly long half-life (35 h) with a slow renal elimination, allowing for once-a-day administration (11,16,39). The plasma and urine half-lives of rufloxacin are two times longer than those of pefloxacin (4,23).…”
mentioning
confidence: 99%
“…(15). It has excellent serum and urine concentrations and a particularly long half-life (35 h) with a slow renal elimination, allowing for once-a-day administration (11,16,39). The plasma and urine half-lives of rufloxacin are two times longer than those of pefloxacin (4,23).…”
mentioning
confidence: 99%
“…In vitro, the antibacterial activity of rufloxacin is similar to that of norfloxacin (36), while in animal models it has activity similar to that of ciprofloxacin (12). In humans pharmacokinetic studies have demonstrated that rufloxacin is eliminated slowly, with a half-life in plasma of about 35 h (14,19,37). The drug penetrates well into most body fluids, tissues, and cells, where it reaches high and stable concentrations, ranging from 2 to 25 times those in plasma (4,19,35,37).…”
mentioning
confidence: 99%
“…It is rapidly absorbed by the gastrointestinal tract, with a maximal plasma concentration after 4 h (12) of 3 to 5 mg/liter (12,15) and a plasma half-life of 35 h (12). During multipledose administration, the drug shows an accumulation ratio in plasma ranging from 2.4 to 3.5 (3,15).…”
mentioning
confidence: 99%
“…The individual fluoroquinolones differ in their physiochemical properties, pharmacokinetic characteristics, and body fluid penetration abilities (10,14). Their lipophilicity (octanol-buffer partition coefficient ϭ 0.37 at pH 7) (1, 7) and the high apparent volume of distribution of 130 to 150 liters (12,15,26,28) account for their high degree of penetration into CSF. However, analysis of comparative data on CSF transport and disposition of quinolones distinguishes between agents with high (e.g., pefloxacin) and low (e.g., ciprofloxacin) levels of availability to the CSF (11,13,21).…”
mentioning
confidence: 99%